Git version control cookbook : leverage version control to transform your development workflow and boost productivity /: leverage version control to transform your development workflow and boost productivity. (2018) - Geisshirt, Kenneth; Zattin, Emanuele; Voss, Rasmus; Olsson, Aske
No abstract available